The influence of store atmosphere and display layout on customer repurchase intention in supermarket (a survey in Jawa Barat Province, Indonesia) - Mei Andriani Situmorang; Suresh Kumar (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
The purpose of this study is to identify the factors which influence customer repurchase intention based on store atmosphere and store display layout. This study applied a survey method which was distributed in the form of a questionnaire as the instrument tool. By using the purposive sampling technique, the questionnaire was filled up by 400 respondents who were usually shopping at a supermarket in the Bekasi region, Indonesia. The data collected were analyzed with the structural equation model. This research revealed that repurchase intention was affected by store atmosphere, which comprises six sub-dimensions: cleanliness, music, scent, temperature, lighting, and color. Store display layout which also divided into three sub-dimensions; product assortment, store design/layout, and window display. It was found that both variables, store atmosphere and display layout play a significant role in affecting repurchase intention in supermarkets. This study was the first study that assessed whether store atmosphere and display/layout have a significant impact on customers' repurchase buying in the supermarket context.